2011
DOI: 10.4049/jimmunol.1101727
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with Costimulatory Dendritic Cells To Control Autoimmune Inflammation

Abstract: Costimulation-deficient dendritic cells (DCs) prevent autoimmune disease in mouse models. However, autoimmune-prone mice and humans fail to control expansion of peripheral autoreactive effector memory T cells (TEMs), which resist immunoregulation by costimulation-deficient DCs. In contrast, activation of DC costimulation may be coupled with regulatory capacity. To test whether costimulatory DCs control TEMs and attenuate established autoimmune disease, we used RelB-deficient mice, which have multiorgan inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 84 publications
1
29
0
Order By: Relevance
“…In addition, the expression of CD40 on DCs is important for T-cell priming and T-cell-mediated effector function. 32 LPS-stimulated human or mice moDCs display a strong expression of the maturation markers CD40 and CD86, 31,33 which is in agreement with this study. We identified that the costimulatory molecules were up-regulated in both moDCs and SDCs, whereas moDCs were induced to be more mature than SDCs following LPS stimulation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the expression of CD40 on DCs is important for T-cell priming and T-cell-mediated effector function. 32 LPS-stimulated human or mice moDCs display a strong expression of the maturation markers CD40 and CD86, 31,33 which is in agreement with this study. We identified that the costimulatory molecules were up-regulated in both moDCs and SDCs, whereas moDCs were induced to be more mature than SDCs following LPS stimulation.…”
Section: Discussionsupporting
confidence: 93%
“…30 It is well-described that CD80/86 through CD28 increase pro-inflammatory cytokine production in T-cells. 31 CD86 was found to be up-regulated on the cell surface of DCs, suggesting that it interacted with CD28, thereby promoting T-cell activation and maturation. In addition, the expression of CD40 on DCs is important for T-cell priming and T-cell-mediated effector function.…”
Section: Discussionmentioning
confidence: 97%
“…The underlying mechanisms remain to be explored. Foxp3 + Treg homeostasis is likely enforced by inflammation which e.g., causes the increased expression of MHC-class-II, CD80, CD86, and IL-2 (Oldenhove et al, 2003; Yamazaki et al, 2003; Banerjee et al, 2006; O'Sullivan et al, 2011). In summary, DCs critically regulate the homeostasis and activation state of Foxp3 + Tregs.…”
Section: Layers Of Dc-mediated Tolerancementioning
confidence: 99%
“…1 Although normal T reg cell numbers were observed in the periphery, this restoration is likely due to the potent homeostatic mechanisms that normally restore T reg cell deficits. 6 Collectively, these findings challenge the notion that conventional thymocyte maturation requires the thymic medulla, but what about immunological tolerance? Young Foxn1 Cre Traf6 fl/fl mice initially appeared normal, but then lost weight and their health deteriorated after 6 months of age.…”
mentioning
confidence: 99%
“…The transcriptional activity of RelB in immature DCs is low, and indeed Treg are increased in RelB-deficient mice and induced by transfer of RelB-deficient DCs to wild-type hosts. 4,6 Far from a state of immunosuppression though, naive T cells in the resting state require persistent low-level MHC peptide-mediated signalling for their survival and this constitutive signalling by resting DCs promotes T-cell sensitivity to immunogenic antigen presentation. 7 Second, peripheral tolerance must regulate the immune response to a variety of inflammatory signals, including pathogen-derived endotoxin, endogenous cytokines, proinflammatory toxins and tumour environment and damage-associated molecules.…”
mentioning
confidence: 99%